Loneliness: Thoughts on its relation with psychopathology and psychotherapy - Galanaki, Evangelia (Encephalos, 2014)
In this paper we examine the relation of loneliness with psychopathology and psychotherapy. More specifically, first we present interpretations about the long-standing neglect of loneliness by the disciplines of Psychology and Psychiatry. Next, we analyze psychoanalytic and existential views from the clinical field about the associations between loneliness and psychopathology. We focus on narcissistic trauma and incapacity for love, as accompanying aspects of loneliness in many forms of psychopathology. Also, we discuss the role of loneliness in the psychotherapeutic relationship, according to the aforementioned views. Finally, we propose that we should recognize the paradoxical nature of loneliness, which means that this experience has both distressing and beneficial aspects, and that apart from being an inescapable universal condition, it may become an index of psychopathology as well.